Endodontic Management of a Maxillary Molar with Three Mesiobuccal Canals - Sirisha Gundam; Radhika Maddu; Sindhura Reddy Gurram (Case Reports in Dentistry)
It is imperative that the clinician should have comprehensive knowledge about the normal anatomy and its variations of the teeth as the deviations from the usual are very common. An increased awareness of unusual anatomy and a better understanding of the root canal system guide the clinician in accurate diagnosis and treatment of such variations in order to achieve a successful endodontic outcome. The maxillary first molar has been shown to have a wide variation in respect to the number of canals specifically noted in the mesiobuccal root. The current case report shows the successful management of a maxillary molar in which the mesiobuccal root had three canals.